Electronic catalogue of the cometary physical characteristics - Andrienko, J.; Reshetnyk, V. (Advances in Astronomy and Space Physics, 2012)
Lack of the new catalogues of the physical characteristics of comets (the last one was published in 1985) was the reason of our work. Vsehsvyatskiy and Andrienko catalogues of the physical characteristics of comets from 1950 to 1985 and the data on the comets orbital elements of Jet Propulsion Laboratory NASA were used for compilation of our electronic catalogue. The special software was developed for this task. The input data were identified, corrected and transformed to the unified format. The data from IAU Central Bureau for Astronomical Telegrams from 1969 to 2008 years were used for determination of the comets visual magnitudes. We obtained the apparent magnitudes for 943 comets. Some of them were used for the comet absolute magnitude calculation. The main criterion for determination of the absolute magnitude was the presence of enough data on their apparent magnitudes. We also obtained the light curves for some comets.